Specific Anti-SARS-CoV-2 Humoral and Cellular Immune Responses After Booster Dose of BNT162b2 Pfizer-BioNTech mRNA-Based Vaccine: Integrated Study of Adaptive Immune System Components - Busà, Rosalia; Sorrentino, Maria Concetta; Russelli, Giovanna; Amico, Giandomenico; Miceli, Vitale; Miele, Monica; Di Bella, Mariangela; Timoneri, Francesca; Gallo, Alessia; Zito, Giovanni; Di Carlo, Daniele; Conaldi, Pier Giulio; et al. (Frontiers in Immunology, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19) is modifying human activity all over the world with significant health and economic burden. The advent of the SARS-CoV-2 pandemic, prompted the scientific community to learn the virus dynamics concerning transmissibility, epidemiology, and usefulness of vaccines in fighting emerging health hazards. Pieces of evidence suggest that the first and second dose of mRNA vaccines, induces a significant antibody response in vaccinated subjects or patients who recovered from SARS-CoV-2 infection, demonstrating the importance of the previously formed memory. The aim of this work has been to investigate the effects of BNT162b2 Pfizer-BioNTech mRNA-based vaccine booster dose in a cohort of 11 uninfected immunocompetent (ICs), evaluating the humoral and cellular responses, with more carefulness on memory B and T cells. Our findings underscore the potential benefit of the third dose of mRNA vaccine on the lifespan of memory B and T cells, suggesting that booster doses could increase protection against SARS-CoV-2 infection.